Surgical management of primary thyroid tumours. Issue 3 (March 2018) - Asimakopoulos, P.; Nixon, I.J.
Abstract: The majority of patients who present with well differentiated thyroid cancer will require surgery, but decisions on the appropriate primary procedure will depend on information relating to patient, tumour and surgical factors. As the incidence of thyroid cancer continues to rise, it is critical that clinicians involved in the management of these cases understand the factors which underpin surgical decision making for individual patients. Reporting outcomes in well differentiated thyroid cancer (WDTC) has always been challenging due to the low recurrence and mortality rate of the disease. Although early data supported total thyroidectomy for all patients with >1 cm WDTC, more recent evidence has supported lobectomy in selected, low risk patients. As a result we have seen a change in the approach of international guidelines from a blanket statement that total thyroidectomy should be the treatment for all patients towards a more selective approach to therapy. When selecting the most appropriate surgical approach to WDTC, the primary aim is to minimize the chance of death from disease or further recurrence. Additionally the impact of potential side effects of treatment (laryngeal nerve injury and hypocalcaemia) must also be weighed in the balance. In this review of surgical management of WDTC we aim to present a historical perspective on this subject and explore the arguments for and against total thyroidectomy and thyroid lobectomy in the low-risk patient group.